Gender differences in Internet perceptions and use. - FORD, Nigel (1996)
Explores the perception and reported usage of the Internet in relation to individual differences among higher education students. Reports that the clearest findings related to gender differences, with females reporting significantly greater levels of disorientation and disenchantment in relation to the Internet.